The Severity of Muscle Performance Deterioration in Sarcopenia Correlates With Circulating Muscle Tissue-Specific miRNAs - Valášková, S; Gažová, A; Vrbová, P; Koller, T; Šalingova, B; Adamičková, A; Chomaničová, N; Hulajová, N; Payer, J; Kyselovič, J (Physiological research, 2021)
Sarcopenia is defined as an age-associated loss of skeletal muscle function and muscle mass and is common in older adults. Sarcopenia as a disease is currently of interest not only to orthopedists and surgeons but also to internists, endocrinologists, rheumatologists, cardiologists, diabetologists, gynaecologists, geriatricians and paediatricians. In cooperation with the 5th Internal Medicine Clinic, we, as a unit of clinical research, aimed to describe a sarcopenic specific miRNA expression profile for disease diagnostics and classification of the severity of muscle performance deterioration. This study included a total of 80 patients (age 55-86 years) hospitalized at the V. Internal medicine clinic of LFUK and UNB with different severity of muscle performance deterioration. The study participants were evaluated and classified according to short physical performance battery score (SPPB). In this study, we investigated the role of circulating miRNAs in sarcopenia in the elderly. We hypothesized that sarcopenia effects the expression of muscle tissue-specific miRNAs (MyomiRNAs), which could be potentially reflected in the blood plasma miRNA expression profile. The expression of specific circulating miRNAs in patients with different muscle performances was analyzed. Patients' blood plasma was evaluated for the expression of myomiRNAs: miRNA-29a, miRNA-29b, miRNA-1, miRNA-133a, miRNA-133b, miRNA-206, miRNA-208b and miRNA-499, and the data were correlated with diagnostic indicators of the disease. We showed a specific sarcopenia miRNA profile that could be considered a possible biomarker for the disease. Patients with low muscle performance showed increased miRNA-1, miRNA-29a and miRNA-29b expression and decreased for the miRNA-206, miRNA-133a, miRNA-133b, miRNA-208b and miRNA-499 expression. We show that the severity of muscle performance deterioration in sarcopenia correlates with specific miRNA expression. We also propose the profile of miRNAs expression in blood plasma as a specific biomarker for sarcopenia diagnostics. Future clinical studies will be necessary to eventually naturally have to elucidate the underlined molecular mechanism responsible for specific miRNAs expression in sarcopenia pathology and progression of the disease.
Keywords: kosterní svaly; Female; biologické markery; Biomarkers; ženské pohlaví; lidé; Aged, 80 and over; Muscle, Skeletal; Physical Examination; Male; Aged; mikro RNA; Sarcopenia; fyzikální vyšetření; MicroRNAs; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; sarkopenie; Middle Aged; Humans